Tackling Drug Resistance in EGFR Exon 20 Insertion Mutant Lung Cancer - Pacini L; Jenks AD; Vyse S; Wilding CP; Arthur A; Huang PH (Dove Medical Press, 2021)
Laura Pacini,* Andrew D Jenks,* Simon Vyse,* Christopher P Wilding, Amani Arthur, Paul H Huang Division of Molecular Pathology, The Institute of Cancer Research, London, UK*These authors contributed equally to this workCorrespondence: Paul H HuangDivision of Molecular Pathology, The Institute of Cancer Research, 237 Fulham Road, London, SW3 6JB, UKTel +44 207 153 5554Email paul.huang@icr.ac.ukAbstract: Insertion mutations in exon 20 (Ex20ins) of the epidermal growth factor receptor (EGFR) gene are the largest class of EGFR mutations in non-small cell lung cancer (NSCLC) for which there are currently no approved targeted therapies. NSCLC patients with these mutations do not respond to clinically approved EGFR tyrosine kinase inhibitors (TKIs) and have poor outcomes. A number of early phase clinical trials are currently underway to evaluate the efficacy of a new generation of TKIs that are capable of binding to and blocking Ex20ins. Although these agents have shown some clinical activity, patient responses have been restricted by dose-limiting toxicity or rapid acquisition of resistance after a short response. Here we review the current understanding of the mechanisms of resistance to these compounds, which include on-target EGFR secondary mutations, compensatory bypass pathway activation and acquisition of an EMT phenotype. Taking lessons from conventional EGFR inhibitor therapy in NSCLC, we also consider other potential sources of resistance including the presence of drug-tolerant persister cells. We will discuss therapeutic strategies which have the potential to overcome different forms of drug resistance. We conclude by evaluating recent technological developments in drug discovery such as PROTACs as a means to better tackle TKI resistance in NSCLC harbouring Ex20ins mutations.Keywords: EGFR, exon 20 insertions, poziotinib, lung cancer, drug resistance, PROTACs